Word Formation and Transparency in Medical English. - Pius ten Hacken, RenÃita PanocovÃi (Cambridge Scholars Publishing, 2015)
As a side effect of the rapid progress in medical research and of the emergence of new medical conditions, medicine is a domain where new concepts have to be named more frequently than in many other domains. Because of the prominent position of English in medical research, most of these concepts are first named in English. This raises questions relating to the naming strategies adopted and the consequences of the choice of particular strategies. These consequences are not restricted to English, because the English terms often need to be translated and are sometimes borrowed.This volume consist.